The Effect of Fixation Technique on Continuous Interscalene Nerve Block Catheter Success: A Randomized, Double-Blind Trial. (March 2017) - Auyong, David B.; Cantor, David Asher; Green, Cynthia; Hanson, Neil A.
Abstract : BACKGROUND: Continuous peripheral nerve blocks offer advantages over single-injection blocks, including extended analgesia and reduction in opioid consumption. These benefits require that the perineural catheter remain intact for the duration of the planned local anesthetic infusion. Mechanical displacement of catheters, leaking, and consequent failure are known complications. The aim of this study was to evaluate continuous perineural catheter tip-to-nerve apposition in vivo over 48 hours comparing 2 different simple fixation strategies. METHODS: Subjects presenting for a continuous interscalene nerve block were randomized to perineural catheter fixation with 1 of 2 types of adhesive: Dermabond (2-octylcyanoacrylate) or Mastisol (alcohol 23A, gum mastic, storax, and methyl salicylate), covered with a simple transparent dressing. The primary outcome was the evaluation of catheter-to-nerve apposition maintenance over 48 hours via both a blinded ultrasound evaluation of local anesthetic distribution and a blinded clinical assessment. Secondary outcomes included leakage at the catheter site, pain scores, opioid consumption, catheter-to-skin migration at the insertion site, and patient satisfaction. RESULTS: Sixty-six subjects were recruited and randomized to compare adhesive group catheter tip-to-nerve apposition on postoperative day 2 (POD 2). Within the intention-to-treat cohort, a statistically significant decrease of perineural catheter tip-to-nerve apposition in the Mastisol group (64.7%) compared with the Dermabond group (90.6%) on POD 2 (odds ratios [OR] 0.19; 95% confidence interval [CI] 0.05–0.75; P = .012) was observed. Similar results were observed on POD 1 (OR 0.19; 95% CI 0.03–1.38; P = NS) and POD 2 (OR 0.14; 95% CI 0.02–0.97; P = .008) within the as-treated cohort. Catheter leakage (OR 67; 95% CI 7.3–589) and median catheter migration difference at the skin insertion site (2.0 cm; 95% CI 0.5–2.5) were also significantly greater in the Mastisol group than in the Dermabond group from POD 0 to POD 2 ( P < .001). Median postoperative opioid consumption difference in morphine equivalents (3.2 mg; 95% CI – 9.0 to 14.2) was not significantly different between the Dermabond and the Mastisol groups through POD 2 ( P = .542). CONCLUSIONS: Perineural catheter fixation with Dermabond in continuous interscalene nerve block improves maintenance of catheter-to-nerve apposition when compared with Mastisol.